A porous composite elastomer, silicon carbon and its preparation method and application

By using a porous composite elastomer structure and CVD vapor phase silicon deposition technology in silicon-carbon materials, the problem of performance degradation caused by volume expansion of silicon-based anode materials during the removal/insertion process of lithium is solved, achieving high rate and high cycle stability. Silicon carbon composite anode material.

CN118156508BActive Publication Date: 2025-01-21CARBON ONE NEW ENERGY GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410244207.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-02-08
Filing Date
2024-03-04
Publication Date
2025-01-21
Estimated Expiration
2044-03-04

AI Technical Summary

Technical Problem

The existing silicon-based anode materials crack and powder due to volume expansion during the de-lithium de-embedding process, resulting in rapid capacity reduction and cyclic attenuation. Simple silicon-carbon recombination cannot guarantee good ion transport performance.

Method used

Using porous composite elastomers, silicon carbon materials are prepared through the composite of carbon nanotubes and hard carbon. Wool-like carbon tubes are used to form macroporous materials to accommodate ordered micro-mesoporous carbon with moderate hardness, and CVD is performed on this substrate. Vapor-phase silicon deposition forms a silicon-carbon composite anode material with good electrical conductivity and ion conductivity.

Benefits of technology

It improves the rate performance and cycle stability of the negative electrode material, reduces the risk of material fracturing during the rolling process of making electrode sheets, and avoids the problem of cycle diving caused by volume expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118156508B_ABST
    Figure CN118156508B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of battery negative electrode materials, and in particular to a porous composite elastomer, silicon carbon, and preparation methods and applications thereof. The present application provides a porous composite elastomer, which is a porous structure, wherein the porous composite elastomer comprises a flexible body and a rigid body interlaced with each other, wherein the raw material of the flexible body comprises carbon nanotubes, and the rigid body comprises hard carbon. The present application uses carbon nanotubes and hard carbon as carbon sources to prepare silicon-carbon composite materials in combination with silicon. Compared with conventional silicon-carbon composite materials, carbon nanotubes serve as a bridge between silicon and hard carbon, effectively improving electrical conductivity and ion conduction energy, thereby improving the rate performance of negative electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery negative electrode materials, and in particular to a porous composite elastomer, silicon carbon, and a preparation method and application thereof. Background Art

[0002] Silicon has an ultra-high theoretical lithium insertion capacity and a moderate lithium extraction / insertion potential, so silicon-based negative electrode materials are undoubtedly the next generation of ideal lithium-ion battery negative electrode materials after graphite. However, silicon has very poor electrical conductivity and ion diffusion coefficient, and in the process of lithium extraction / insertion, silicon will undergo severe volume expansion (>300%), causing the material to crack and pulverize, and fall off from the current collector, resulting in a rapid decrease in capacity and cycle attenuation. Although the existing technology uses carbon materials and silicon composites to alleviate the volume expansion of silicon to a certain extent to improve the cycle performance, this simple physical composite of silicon and carbon cannot guarantee the ion transport performance in the composite material.

[0003] Patent (CN114420928A) discloses a silicon-carbon composite material with a core-shell structure formed by using carbon nanotubes, graphene and nano-silicon as the core material and coating the outer layer with soft carbon. Carbon nanotubes and graphene can improve the ion transmission capacity of the composite material, but the composite of carbon nanotubes, graphene and silicon through grinding cannot ensure the composite uniformity and therefore cannot ensure good bulk ion transmission performance. In addition, silicon exists in the form of microns, and serious volume expansion will occur during the lithium removal / insertion process, which will cause the battery cycle performance to plummet. Patent (CN115663131A) uses CVD vapor deposition to deposit nano-silicon in pelletized carbon nanotubes. The reduction of silicon size alleviates the volume expansion. However, the pores of the spherical carbon nanotubes after shaping are very large, so silicon is easy to agglomerate during the deposition process. In addition, the hardness difference between carbon nanotubes and silicon is large. The rolling process of preparing the pole piece will cause the material to be broken and the volume expansion during the lithium removal / insertion process will cause the material to pulverize and cause the cycle to plummet. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the purpose of the present application is to provide a porous composite elastomer, silicon carbon and a preparation method and application thereof.

[0005] To achieve the above-mentioned purpose and other related purposes, the present invention is prepared by including the following technical solutions.

[0006] In a first aspect, the present application provides a porous composite elastomer, which is a porous structure. The porous composite elastomer includes a flexible body and a rigid body that are interpenetrating with each other. The raw material of the flexible body includes carbon nanotubes, and the rigid body is hard carbon.

[0007] In any embodiment of the present application, the porous composite elastomer contains uniformly distributed micropores and / or mesopores.

[0008] In any embodiment of the present application, the mass ratio of the flexible body to the rigid body is (0.01-2): 1. Preferably, the mass ratio of the flexible body to the rigid body is (0.8-1.2):1.

[0009] In any embodiment of the present application, the average pore size of the porous composite elastomer is <15 nm, preferably 1.8 to 10 nm.

[0010] In any embodiment of the present application, the total pore volume of the porous composite elastomer is 0.2 to 1.5 cm 3 / g, preferably 0.4 to 1.1 cm 3 / g.

[0011] In any embodiment of the present application, the specific surface area of ​​the porous composite elastomer is> 200m 2 / g, preferably >700m 2 / g.

[0012] In any embodiment of the present application, D of the porous composite elastomer 50 It is <30 μm, preferably <20 μm.

[0013] In any embodiment of the present application, the tap density of the porous composite elastomer is 0.1 to 1.0 g / cm 3 , preferably 0.2 to 0.7 g / cm 3 .

[0014] In any embodiment of the present application, the resistivity of the porous composite elastomer is <5Ω·cm, preferably <0.5Ω·cm, and further preferably <0.05Ω·cm.

[0015] In any embodiment of the present application, the pore size concentration of the porous composite elastomer is less than 7, preferably 0.5-5.

[0016] The second aspect of the present application provides a method for preparing the aforementioned porous composite elastomer, comprising the following steps:

[0017] S1: Preparation of carbon tube clusters: shaping carbon nanotubes to form carbon tube clusters;

[0018] S2: Preparation of carbon tube composite carbon material: adding carbon tube clusters into a solution containing a soft template and a polymer, allowing the solution to penetrate into the carbon tube clusters, and heat treating to obtain the carbon tube composite carbon material;

[0019] S3: Preparation of porous composite elastomer: Carbonizing the carbon tube composite carbon material to obtain a porous composite elastomer.

[0020] In any embodiment of the present application, in step S1, the shaping is performed by a shaping machine. Preferably, the main machine frequency of the shaping machine is 5 to 60 Hz, the auxiliary machine frequency is 20 to 90 Hz, the fan frequency is 8 to 30 Hz, and the operation time is 2 to 100 min.

[0021] In any embodiment of the present application, in step S1, the carbon nanotube has a length of 0.1 to 50 μm and a tube diameter of 2 to 20 nm.

[0022] In any embodiment of the present application, in step S1, the D of the carbon tube cluster 50 1~100μm.

[0023] In any embodiment of the present application, in step S1, the carbon tube cluster is a woolen ball structure. Preferably, the shaped carbon tube cluster is spherical or quasi-spherical, and the sphericity Sh(10%) of the carbon tube cluster is ≥0.70, the sphericity Sh(50%) is ≥0.80, and the sphericity Sh(90%) is ≥0.85.

[0024] In any embodiment of the present application, an intermediate modification treatment is further included between step S1 and step S2: adding the carbon tube clusters into an acidic solution and stirring, filtering to obtain a solid, washing to neutrality, and drying to obtain a modified carbon tube cluster.

[0025] In any embodiment of the present application, the mass ratio of the carbon tube clusters to the acidic solution is (0.1-100):1.

[0026] In any embodiment of the present application, the acidic solution is selected from one or more of nitric acid, sulfuric acid, and hydrochloric acid.

[0027] In any embodiment of the present application, the stirring reaction temperature is 30 to 100° C., and the stirring reaction time is 2 to 12 h.

[0028] In any embodiment of the present application, washing is performed with pure water, and drying is performed in a drying oven at a drying temperature of 60 to 100° C. and a drying time of 2 to 48 hours.

[0029] In any embodiment of the present application, in step S2, the polymer is selected from Formula I:

[0030]

[0031] wherein A1 is selected from X, OH, NH2 or a benzene ring substituted by X, OH or NH2; X is selected from the halide of F, Cl, Br and I; R1, R2 and R3 are independently selected from H, unsubstituted or substituted phenyl, unsubstituted or substituted C1-C 20 Alkyl, unsubstituted or substituted C1-C 20at least one of the alkoxy groups; a substituent group in a substituted phenyl group, a substituted C1-C 20 Substituents in alkyl groups and substituted C1-C 20 The substituent groups in the alkoxy group are independently selected from at least one of halogen, OH or NH2. The polymer is selected from one or more of polyethylene glycol, waterborne polyurethane, polyvinylidene fluoride, fluorinated copolymer, polyimide, polyacrylic acid, polyacrylate, polymethyl methacrylate, phenolic resin, epoxy resin, or ionic resin.

[0032] In any embodiment of the present application, in step S2, the soft template is selected from a nonionic surfactant or an ionic surfactant. Preferably, the nonionic surfactant is selected from a polyoxyethylene-polyoxypropylene copolymer; and the ionic surfactant is selected from hexadecyltrimethylammonium bromide and / or sodium dodecylsulfonate.

[0033] In any embodiment of the present application, in step S2, the mass ratio of the carbon tube clusters to the polymer is (0.1-10): 1. Preferably, the mass ratio of the carbon tube clusters to the polymer is 1:3.

[0034] In any embodiment of the present application, in step S2, the solid content of the polymer in the solution is 20-100%.

[0035] In any embodiment of the present application, in step S2, the solution infiltrates into the carbon tube mass under negative pressure conditions, the negative pressure conditions are -0.9 to -0.01 MPa, and the negative pressure time is 0.5 to 10 hours. After the negative pressure treatment, positive pressure treatment is also included; the positive pressure conditions are 0.15 to 2 MPa, and the pressure holding time is 0.5 to 48 hours.

[0036] In any embodiment of the present application, in step S2, the solvent needs to be evaporated after the heat treatment to obtain a carbon tube composite carbon material, and the heat treatment temperature is 80 to 200° C. and the heat treatment time is 0.5 to 50 hours.

[0037] In any embodiment of the present application, in step S3, the carbonization treatment includes subjecting the carbon tube composite carbon material to a high temperature reaction under a protective gas.

[0038] In any embodiment of the present application, the protective gas in the carbonization treatment is selected from one or more of nitrogen, neon, argon, krypton, xenon, and radon, and the flow rate of the protective gas is 1 to 20 L / min.

[0039] In any embodiment of the present application, the temperature of the high temperature reaction is 500-1000° C., the time of the high temperature reaction is 1-30 hours, and the heating rate is 1-10° C. / min.

[0040] In any embodiment of the present application, the high temperature reaction further includes a post-treatment step: cooling to room temperature.

[0041] The third aspect of the present application provides a silicon carbon, the raw materials of which include the aforementioned porous composite elastomer and also include nano silicon particles.

[0042] In any embodiment of the present application, the nano-silicon particles are embedded in the porous composite elastomer, and the silicon carbon contains uniformly distributed micropores and / or mesopores.

[0043] In any embodiment of the present application, the specific surface area of ​​the silicon carbon is less than 20m 2 / g.

[0044] In any embodiment of the present application, the D of the silicon carbon 50 The tap density of the silicon carbon is 0.5 to 2 g / cm 3 .

[0045] In any embodiment of the present application, the content of the nano silicon particles is 30-70% of the total mass of the silicon carbon. The resistivity of the silicon carbon is less than 20Ω·cm.

[0046] In any embodiment of the present application, the specific capacity of the silicon carbon is greater than 1200 mAh / g, the first coulombic efficiency is greater than 89%, the capacity retention rate after 500 cycles is greater than 85%, and the 4C / 1C rate performance is greater than 90%.

[0047] The fourth aspect of the present application provides a method for preparing the aforementioned silicon carbon, comprising: vapor deposition of a porous composite elastomer and a silicon-containing source gas in a high temperature environment to obtain silicon carbon.

[0048] In any embodiment of the present application, the high temperature environment is a deposition furnace, the high temperature is 300-600°C, and the insulation time is 1-50h; preferably, the pressure in the deposition furnace is maintained at 5-10MPa, and the heating rate is 1-5°C / min.

[0049] In any embodiment of the present application, the silicon source gas is selected from one or more of monosilane, disilane, dichlorosilane, and trichlorosilane; the carbon source gas is selected from alkane gases with a cracking temperature below 600°C.

[0050] In any embodiment of the present application, the silicon-containing source gas further includes a carbon source gas.

[0051] In any embodiment of the present application, the time of vapor deposition is 1 to 50 hours. Preferably, the time of vapor deposition is 10 to 30 hours.

[0052] In any embodiment of the present application, when the silicon-containing source gas is only the silicon source gas, the gas flow rate is 1 to 20 L / min.

[0053] In any embodiment of the present application, when the silicon-containing source gas includes a silicon source gas and a carbon source gas, based on the total volume of the gas, the volume proportion of the silicon source gas is 70 to 99%, and the volume proportion of the carbon source gas is 1 to 30%; the gas flow rate is 5 to 20 L / min.

[0054] A fifth aspect of the present application provides a carbon-coated silicon carbon, comprising the aforementioned silicon carbon and a carbon coating layer coated on the surface of the silicon carbon.

[0055] In any embodiment of the present application, the carbon coating amount of the carbon-coated silicon-carbon is 0.5-10 wt %. Preferably, the carbon coating amount of the carbon-coated silicon-carbon is 0.5-5 wt %.

[0056] In any embodiment of the present application, the median particle size D of the carbon-coated silicon carbon is 50 is <20μm.

[0057] In any embodiment of the present application, the content of silicon in the carbon-coated silicon carbon is 20-80 wt %.

[0058] In any embodiment of the present application, the specific surface area of ​​the carbon-coated silicon carbon is 0.5 to 20.0 m 2 / g.

[0059] In any embodiment of the present application, the compaction density of the carbon-coated silicon carbon powder is 0.5 to 2 g / cm 3 .

[0060] A sixth aspect of the present application provides a method for preparing the aforementioned carbon-coated silicon carbon, comprising introducing a mixed gas comprising a protective gas and a carbon source gas to coat the silicon carbon to form carbon-coated silicon carbon.

[0061] In any embodiment of the present application, the carbon source gas is selected from alkane gases having a cracking temperature below 600°C.

[0062] In any embodiment of the present application, the protective gas is selected from one or more of nitrogen, neon, argon, krypton, xenon, and radon.

[0063] In any embodiment of the present application, based on the total volume of the mixed gas, the volume of the carbon source gas accounts for 60-80%, and the volume of the protective gas accounts for 20-40%. The gas flow rate of the mixed gas is 0.1-50 L / min, preferably 5-20 L / min.

[0064] A seventh aspect of the present application provides a silicon-carbon composite negative electrode material, the raw materials of which include the aforementioned porous composite elastomer, the aforementioned silicon-carbon, or the aforementioned carbon-coated silicon-carbon.

[0065] An eighth aspect of the present application provides the use of the aforementioned porous composite elastomer, the aforementioned silicon-carbon, the aforementioned carbon-coated silicon-carbon, or the aforementioned silicon-carbon composite negative electrode material in the preparation of battery products.

[0066] A ninth aspect of the present application provides a lithium-ion battery, the raw materials of which include the aforementioned porous composite elastomer, the aforementioned silicon-carbon, the aforementioned carbon-coated silicon-carbon, or the aforementioned silicon-carbon composite negative electrode material.

[0067] Compared with the prior art, the beneficial effects of this application are:

[0068] 1. In the present application, carbon nanotubes and hard carbon are used as carbon sources to prepare silicon-carbon composite materials with silicon. Compared with conventional silicon-carbon composite materials, carbon nanotubes serve as a bridge between silicon and hard carbon, effectively improving the electrical conductivity and ion conduction energy, thereby improving the rate performance of the negative electrode material.

[0069] 2. This application uses wool-like carbon tubes to form macroporous materials to accommodate ordered micro-mesoporous carbon with moderate hardness, and then uses micro-mesoporous materials to accommodate single nano-silicon with excessive hardness. On the one hand, the ordered micro-mesoporous carbon with higher strength belongs to hard carbon, which makes the composite material have higher strength, which can greatly reduce the risk of the negative electrode material being crushed during the rolling process of the pole piece, and improve the safety performance of the pole piece preparation; on the other hand, the flexible carbon tubes make the composite material have certain elasticity and ductility, which can prevent the composite material from falling off from the pole piece due to volume expansion during the charge and discharge process, thereby avoiding the problem of battery cycle diving.

[0070] 3. The present application uses a soft template method to form pores, and achieves pore formation through a simple heating process. Compared with the existing activated pore formation technology, it greatly simplifies the preparation process of porous carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1 Schematic diagram of the preparation process of silicon carbon in this application.

[0072] Figure 2 This is a SEM image of the CNT cluster of the present application.

[0073] Figure 3 This is the SEM image of the CNT composite carbon material of the present application.

[0074] Figure 4 This is the SEM picture of the porous composite elastomer of the present application.

[0075] Figure 5 This is the SEM image of silicon carbon in this application. DETAILED DESCRIPTION

[0076] In order to make the invention purpose, technical scheme and beneficial effect of the present application clearer, the present application is further described below in conjunction with the examples. It should be understood that the examples are only used to explain the present application and are not used to limit the scope of the application. The test methods used in the following examples are conventional methods unless otherwise specified, and those familiar with the technology can easily understand other advantages and effects of the present application from the contents disclosed in this description.

[0077] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0078] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0079] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.

[0080] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, any methods, equipment, and materials of the prior art that are similar or equivalent to the methods, equipment, and materials in the embodiments of the present invention may be used to implement the present invention, based on the prior art mastery of those skilled in the art and the description of the present invention.

[0081] After extensive exploration and research, the inventors of this application have discovered a high-cycle and high-rate silicon-carbon composite negative electrode material and its preparation method. This application first winds carbon nanotubes into a microsphere or microsphere-like structure of a super-large-pore wool ball. The carbon tubes are interconnected, which can guarantee the ion-conducting and electrical-conducting properties to the greatest extent; then use a polymer carbon source material mixed with a soft template to fill the loose large pores of the wool ball, and form a CNT ordered micro / mesoporous carbon skeleton through low-temperature curing and high-temperature carbonization pore formation, and then CVD vapor phase silicon deposition is performed on this base skeleton to prepare a silicon-carbon composite negative electrode material. The material contains abundant carbon nanotubes, so it has good ion and electron transport properties; the material is filled with disordered carbon materials on the basis of flexible carbon nanotubes so that the strength of the composite structure is guaranteed to a certain extent, and the disordered carbon is templated to form pores to obtain a CNT ordered porous carbon composite material by high-temperature carbonization. CVD vapor phase silicon deposition is performed on the basis of this ordered porous material to ensure the uniform compounding of elemental silicon.

[0082] The first aspect of the present application provides a porous composite elastomer, which is a porous structure, wherein the porous composite elastomer includes a flexible body and a rigid body interlaced with each other, the raw material of the flexible body includes carbon nanotubes, and the rigid body includes hard carbon. Among them, the mass ratio of the flexible body to the rigid body is (0.01-2):1. Specifically, it can be (0.01-0.5):1, (0.5-1.0):1, (1.0-1.5):1 or (1.5-2.0):1, etc. Preferably, the mass ratio of the flexible body to the rigid body is (0.8-1.2):1. In a specific embodiment of the present application, the length of the carbon nanotube is 0.1-50 μm, specifically 0.1-1 μm, 1-10 μm, 10-20 μm, 20-30 μm, 30-40 μm, or 40-50 μm, etc. The diameter of the carbon tube is 2-20 nm, specifically 2-10 nm, 10-15 nm, or 15-20 nm. 50 The thickness may be 1 to 100 μm, and specifically, may be 1 to 10 μm, 10 to 50 μm, or 50 to 100 μm.

[0083] The porous composite elastomer provided in the present application contains uniformly distributed micropores and / or mesopores. The average pore size of the porous composite elastomer is <15 nm, preferably 1.8 to 10 nm. The total pore volume is 0.2 to 1.5 cm3 / g, preferably 0.4 to 1.1 cm 3 / g. The specific surface area of ​​porous composite elastomer is>200m 2 / g, preferably >700m 2 / g; more preferably, 600 to 1200 m 2 / g. D of porous composite elastomer 50 The tap density of the porous composite elastomer is 0.1 to 1.0 g / cm 3 , preferably 0.2 to 0.7 g / cm 3 The resistivity of the porous composite elastomer is less than 5Ω·cm, preferably less than 0.5Ω·cm, and more preferably less than 0.05Ω·cm. The pore size concentration of the porous composite elastomer is less than 7, preferably 0.5 to 5, and the pore size concentration = (V 90 -V 10 ) / V 50 , where V 10 It refers to the pore size corresponding to the pore volume distribution percentage reaching 10%, V 50 It refers to the pore size corresponding to the pore volume distribution percentage reaching 50%, V 90 It refers to the pore size corresponding to when the pore volume distribution percentage reaches 90%.

[0084] The second aspect of the present application provides a method for preparing the aforementioned porous composite elastomer, comprising the following steps:

[0085] S1: Preparation of carbon tube clusters: shaping carbon nanotubes to form carbon tube clusters;

[0086] S2: Preparation of carbon tube composite carbon material: adding carbon tube clusters into a solution containing a soft template and a polymer, allowing the solution to penetrate into the carbon tube clusters, and heat treating to obtain the carbon tube composite carbon material;

[0087] S3: Preparation of porous composite elastomer: Carbonizing the carbon tube composite carbon material to obtain a porous composite elastomer.

[0088] In any embodiment of the present application, step S1 refers to the preparation of carbon tube clusters: shaping carbon nanotubes to form carbon tube clusters.

[0089] In the preparation method provided in the present application, in step S1, the shaping is performed by a shaping machine. Preferably, the main machine frequency of the shaping machine is 5 to 60 Hz, specifically 5 to 10 Hz, 10 to 20 Hz, or 20 to 60 Hz, etc.; the auxiliary machine frequency is 20 to 90 Hz, specifically 20 to 30 Hz, 30 to 50 Hz, or 50 to 90 Hz, etc. The fan frequency is 8 to 30 Hz, specifically 8 to 10 Hz, 10 to 20 Hz, or 20 to 30 Hz, etc. The operation time is 2 to 100 min, specifically 2 to 10 min, 10 to 50 min, or 50 to 100 min, etc.

[0090] In the preparation method provided in the present application, in step S1, the length of the carbon nanotubes is 0.1 to 50 μm, specifically 0.1 to 1 μm, 1 to 10 μm, 10 to 20 μm, 20 to 30 μm, 30 to 40 μm, or 40 to 50 μm, etc. The diameter of the tube is 2 to 20 nm, specifically 2 to 10 nm, 10 to 15 nm, or 15 to 20 nm, etc. The median particle size D of the carbon nanotube clusters is 50 It is 1 to 100 μm, specifically 1 to 10 μm, 10 to 50 μm, or 50 to 100 μm, etc. The carbon tube cluster after shaping is a wool ball-like structure. Preferably, the carbon tube cluster after shaping is spherical or quasi-spherical, and the sphericity Sh (10%) of the carbon tube cluster is ≥ 0.70, the sphericity Sh (50%) is ≥ 0.80, and the sphericity Sh (90%) is ≥ 0.85, wherein the sphericity Sh (10%) refers to the sphericity corresponding to the particle size distribution percentage reaching 10%, the sphericity Sh (50%) refers to the sphericity corresponding to the particle size distribution percentage reaching 50%, and the sphericity Sh (90%) refers to the sphericity corresponding to the particle size distribution percentage reaching 90%.

[0091] In the preparation method provided in the present application, an intermediate modification treatment is also included between step S1 and step S2: adding the carbon tube clusters to an acidic solution, reflux stirring, filtering to obtain a solid, washing to neutrality, and drying to obtain a modified carbon tube cluster. Wherein, the mass ratio of the carbon tube clusters to the acidic solution is (0.1-100):1; specifically, it can be (0.1-10):1, (10-50):1, or (50-100):1, etc.

[0092] In the preparation method provided in the present application, the acidic solution is selected from a combination of one or more of nitric acid, sulfuric acid and hydrochloric acid. The stirring reaction temperature is 30-100°C, specifically 30-40°C, 40-50°C, or 50-100°C, etc.; the stirring reaction time is 2-12h, specifically 2-4h, 4-8h, or 8-12h, etc. Washing is carried out with pure water; drying is carried out in a drying oven. The drying temperature is 60-100°C, specifically 60-70°C, 70-80°C, or 80-100°C, etc.; the drying time is 2-48h, specifically 2-12h, 12-24h, or 24-48h, etc. The role of the intermediate modification treatment is to modify the carbon tube clusters. The modified carbon tube clusters will produce carboxyl, amino and other groups. When modified to carboxyl, -NH2 or -OH in the polymer can be loaded, and the loading is carried out by chemical bonding or physical bonding.

[0093] In the preparation method provided in the present application, step S2 refers to the preparation of carbon tube composite carbon material: adding carbon tube clusters into a solution containing a soft template and a polymer, allowing the solution to penetrate into the carbon tube clusters, and heat treating to obtain the carbon tube composite carbon material.

[0094] In the preparation method provided in the present application, a polymer with a specific group is used, and the carbon tube cluster needs to be subjected to an intermediate modification treatment so that the polymer fills the pores of the carbon tube cluster through chemical bonding or hydrogen bonding. The polymer used when the intermediate modification treatment is required is selected from Formula I:

[0095]

[0096] wherein A1 is selected from X, OH, NH2 or a benzene ring substituted by X, OH or NH2; X is selected from the halide of F, Cl, Br and I; R1, R2 and R3 are independently selected from H, unsubstituted or substituted phenyl, unsubstituted or substituted C1-C 20 Alkyl, unsubstituted or substituted C1-C 20 at least one of the alkoxy groups; a substituent group in a substituted phenyl group, a substituted C1-C 20 Substituents in alkyl groups and substituted C1-C 20 The substituent groups in the alkoxy group are independently selected from at least one of halogen, OH or NH2. The polymer is selected from one or more of polyethylene glycol, waterborne polyurethane, polyvinylidene fluoride, fluorinated copolymer, polyimide, polyacrylic acid, polyacrylate, polymethyl methacrylate, phenolic resin, epoxy resin or ionic resin; preferably, the fluorinated copolymer is selected from the copolymer of 1,1-difluoroethylene and hexafluoroethylene.

[0097] In the preparation method provided in the present application, in step S2, when the polymer is selected as one or more of phenolic resin, epoxy resin or ionic resin, it can be selected from carbon tube clusters that have undergone intermediate modification or carbon tube clusters that have not undergone modification. The polymer here can be filled in the pores of the carbon tube clusters through curing.

[0098] In the preparation method provided by the present application, in step S2, the soft template is selected from a non-ionic surfactant or an ionic surfactant; preferably, the non-ionic surfactant is selected from a polyoxyethylene-polyoxypropylene copolymer; the ionic surfactant is selected from hexadecyltrimethylammonium bromide and / or sodium dodecylsulfonate; more preferably, the non-ionic surfactant is selected from F108, F127, F68, or Pluronic and other reagents.

[0099] In the preparation method provided by the present application, in step S2, the mass ratio of the carbon tube clusters to the polymer is (0.1-10):1, specifically (0.1-1):1, (1-5):1, or (5-10):1, etc. In a preferred embodiment of the present application, the mass ratio of the carbon tube clusters to the polymer is 1:3.

[0100] In the preparation method provided in the present application, in step S2, the solid content of the polymer in the solution is 20-100%, specifically 20-30%, 30-50%, or 50-100%.

[0101] In the preparation method provided in the present application, in step S2, the solution penetrates into the carbon tube cluster under negative pressure conditions, and the negative pressure conditions are -0.9 to -0.01MPa, specifically -0.9 to -0.1MPa, -0.1 to -0.05MPa, or -0.05 to -0.01MPa, etc.; the negative pressure time is 0.5 to 10h, specifically 0.5 to 1h, 1 to 2h, or 2 to 10h, etc. After negative pressure, positive pressure treatment is also included; the positive pressure condition is 0.15 to 2MPa, and the pressure holding time is 0.5 to 48h. Preferably, the positive pressure condition is 0.6 to 1MPa; the pressure holding time is 2 to 12h.

[0102] In the preparation method provided in the present application, in step S2, the temperature of the heat treatment is 80-200°C, specifically 80-100°C, 100-150°C, or 150-200°C, etc.; the time of the heat treatment is 0.5-50h, specifically 0.5-1h, 1-5h, or 5-50h, etc.

[0103] In the preparation method provided in the present application, step S3 refers to the preparation of a porous composite elastomer: carbonizing the carbon tube composite carbon material to obtain a porous composite elastomer.

[0104] Among them, the carbonization treatment includes carbonizing and forming pores by reacting the carbon tube composite carbon material at high temperature under protective gas. The protective gas in the carbonization treatment is selected from one or more of nitrogen, neon, argon, krypton, xenon, and radon, and the flow rate of the protective gas is 1 to 20 L / min, specifically 1 to 10 L / min, 10 to 15 L / min, or 15 to 20 L / min. The temperature of carbonization and pore formation is 500 to 1000 ° C, specifically 500 to 700 ° C, 700 to 800 ° C or 800 to 1000 ° C. The time of carbonization and pore formation is 1 to 30 h, specifically 1 to 10 h, 10 to 15 h, or 15 to 30 h. The heating rate is 1 to 10 ° C / min, specifically 1 to 3 ° C / min, 3 to 5 ° C / min, or 5 to 10 ° C / min. After the high temperature reaction, a post-treatment step is also included: cooling to room temperature.

[0105] The porous composite elastomer is sponge-like in shape, and its pores are evenly distributed. The reason why step S3 can form pores is that after high-temperature carbonization treatment, the polymer in the carbon tube composite carbon material is thermally decomposed to form hard carbon, which is filled in the gaps of the carbon tube clusters to form a composite elastomer in which hard carbon and carbon tubes are interlaced with each other. And during the high-temperature carbonization process, the polymer thermally decomposes to produce gas, thereby forming pores inside and on the surface of the composite elastomer, and obtaining a composite elastomer with a porous structure. The uniform distribution of pores in this step is determined by temperature and heating rate. This technology uses a soft template method to form pores, and pores are achieved through a simple heating process. Compared with the existing activated pore-forming technology, the preparation process of porous carbon is greatly simplified.

[0106] The third aspect of the present application provides a silicon carbon, the raw materials of which include the aforementioned porous composite elastomer and also include nano silicon particles.

[0107] In the silicon carbon provided in the present application, nano silicon particles are embedded in the porous composite elastomer, and the silicon carbon contains uniformly distributed micropores and / or mesopores. The specific surface area of ​​the silicon carbon is <20m 2 / g. The total pore volume of silicon carbon is <0.05m 2 / g. The silicon carbon D 50 <20 μm; preferably, 100 nm to 12 μm. The tap density of the silicon carbon is 0.5 to 2 g / cm 3 .

[0108] In the silicon carbon provided by the present application, the content of nano silicon particles is 30-70% of the total mass of silicon carbon. The specific capacity of silicon carbon is greater than 1200mAh / g, the first coulombic efficiency is greater than 89%, the capacity retention rate after 500 cycles is greater than 85%, and the 4C / 1C rate performance is greater than 90%. C is used to indicate the battery charge and discharge capacity rate. 1C indicates the current intensity when the battery is fully discharged in one hour. 4C indicates the current intensity when the battery is fully discharged in four hours.

[0109] The fourth aspect of the present application provides the aforementioned method for preparing silicon carbon, comprising: a porous composite elastomer and a silicon-containing source gas are vapor-deposited in a high-temperature environment to obtain silicon carbon. Wherein, the high-temperature environment is a deposition furnace, the high temperature is 300-600°C, specifically 300-400°C, 400-500°C, or 500-600°C, etc.; the insulation time is 1-50h; specifically 1-10h, 10-20h, or 20-50h, etc.; preferably, the pressure in the deposition furnace is maintained at 5-10MPa, and the heating rate is 1-5°C / min. The silicon-containing source gas is cracked at high temperature, atoms such as H and Cl are volatilized, silicon forms nano-silicon particles, and is deposited in the pores of the porous composite elastomer.

[0110] In the silicon-carbon preparation method provided in the present application, the silicon source gas is selected from one or more of monosilane, disilane, dichlorosilane, and trichlorosilane; the carbon source gas is selected from alkane gases with a cracking temperature below 600°C, preferably, the carbon source gas is selected from acetylene and / or ethylene.

[0111] In the preparation method of silicon-carbon provided in the present application, when the silicon-containing source gas is only a silicon source gas, the gas flow rate is 1 to 20 L / min, specifically 1 to 10 L / min, 10 to 15 L / min, or 15 to 20 L / min, etc.; preferably, 2 to 10 L / min. The silicon-containing source gas also includes a carbon source gas. When the silicon-containing source gas includes a silicon source gas and a carbon source gas, based on the total volume of the gas, the volume proportion of the silicon source gas is 70 to 99%, and the volume proportion of the carbon source gas is 1 to 30%. The total flow rate of the gas is 5 to 20 L / min; specifically, it can be 5 to 10 L / min, 10 to 15 L / min, or 15 to 20 L / min, etc. When the silicon-containing source gas includes a carbon source gas and a silicon source gas, the carbon source gas limits the silicon source gas to prevent all silicon from falling into the same hole.

[0112] A fifth aspect of the present application provides a carbon-coated silicon carbon, comprising the aforementioned silicon carbon and a carbon coating layer coated on the surface of the silicon carbon.

[0113] In the carbon-coated silicon-carbon provided in the present application, the carbon coating amount in the carbon-coated silicon-carbon composite negative electrode material is 0.5 to 10 wt %; preferably, 0.5 to 5 wt %. The median particle size D of the carbon-coated silicon-carbon composite negative electrode material 50 The silicon content is 20-80wt%, and specifically can be 20-30wt%, 30-40wt%, 40-50wt%, 50-60wt%, 60-70wt% or 70-80wt%, etc.; the specific surface area is 0.5-20.0m 2 / g, specifically 0.5 to 10.0 m2 / g, 10.0~15.0m 2 / g, or 15.0~20.0m 2 / g, etc.; pore volume <0.1cm 3 g -1 , the compacted density of the powder is 0.5~2g / cm 3 , specifically 0.5 to 0.7 g / cm 3 , 0.7~0.9g / cm 3 , 0.9~1.2g / cm 3 1.2~1.5g / cm 3 or 1.5~2g / cm 3 wait.

[0114] A sixth aspect of the present application provides a method for preparing the aforementioned carbon-coated silicon carbon, comprising introducing a mixed gas comprising a protective gas and a carbon source gas to coat the silicon carbon to form carbon-coated silicon carbon.

[0115] In the preparation method provided in the present application, the carbon source gas is selected from an alkane gas having a cracking temperature of less than 600°C. Preferably, the carbon source gas is selected from acetylene and / or ethylene. The protective gas is selected from one or more of nitrogen, neon, argon, krypton, xenon, and radon. Based on the total volume of the mixed gas, the volume proportion of the carbon source gas is 60-80%, and the volume proportion of the protective gas is 20-40%; the gas flow rate of the mixed gas is 0.1-50L / min, specifically 0.1-10L / min, 10-20L / min, or 20-50L / min, etc.; preferably, 5-20L / min. The role of the mixed gas is to coat another layer of carbon protective layer.

[0116] The seventh aspect of the present application provides a silicon-carbon composite negative electrode material, the raw materials of which include the aforementioned porous composite elastomer, the aforementioned silicon-carbon, or the aforementioned carbon-coated silicon-carbon. The present technology uses carbon nanotubes and hard carbon as carbon sources to prepare silicon-carbon composite materials with silicon. Compared with conventional silicon-carbon composite materials, carbon nanotubes serve as a bridge between silicon and hard carbon, effectively improving the conductivity and ion conduction energy, thereby improving the rate performance of negative electrode materials. The present application uses wool-like carbon tubes to form macroporous materials to accommodate ordered micro-mesoporous carbon with moderate hardness, and then uses micro-mesoporous materials to accommodate single nano-silicon with excessive hardness. On the one hand, the ordered micro-mesoporous carbon with higher strength belongs to hard carbon, which makes the composite material have higher strength, which can greatly reduce the risk of the negative electrode material being crushed during the rolling process of the electrode sheet, and improve the safety performance of the electrode sheet preparation; on the other hand, the flexible carbon tubes make the composite material have certain elasticity and ductility, which can prevent the composite material from falling off from the electrode sheet due to volume expansion during the charge and discharge process, thereby avoiding the problem of battery cycle diving.

[0117] An eighth aspect of the present application provides the use of the aforementioned porous composite elastomer, the aforementioned silicon-carbon, the aforementioned carbon-coated silicon-carbon, or the aforementioned silicon-carbon composite negative electrode material in the preparation of battery products.

[0118] A ninth aspect of the present application provides a lithium-ion battery, the raw materials of which include the aforementioned porous composite elastomer, the aforementioned silicon-carbon, the aforementioned carbon-coated silicon-carbon, or the aforementioned silicon-carbon composite negative electrode material.

[0119] The present application is further described below by way of examples, but the scope of the present application is not limited thereby.

[0120] Example 1

[0121] (1) CNT agglomerates: Carbon nanotubes with a length of 10 μm and a diameter of 5 nm were shaped by a shaping machine with a main machine frequency of 30 Hz, a secondary machine frequency of 60 Hz, a fan frequency of 10 Hz, and an operation time of 60 min to form a spherical wool ball structure material; the median particle size D of the CNT agglomerates 50 The average pore size is 5.6 μm, the sphericity Sh (10%) is 0.75, the sphericity Sh (50%) is 0.85, and the sphericity Sh (90%) is 0.88; the average pore size is 38.5 nm, and the pore volume is 1.69 cm 3 / g, specific surface area is 175.8m 2 / g, tap density <0.15g / cm 3 , resistivity <0.005Ω·cm;

[0122] (2) Modified CNT agglomerates: Add the woolen carbon nanotubes to a 65% nitric acid solution at a mass ratio of 1:1, and reflux and stir at 100°C for 6 hours; separate and filter to obtain a solid, then wash with pure water until neutral, and then dry in an oven at 80°C for 10 hours to obtain a modified carbon tube agglomerate;

[0123] (3) CNT composite carbon material: CTAB is added to a polyethylene glycol aqueous solution with a solid content of 50%, and then the modified carbon tube clusters are added according to a mass ratio of polyethylene glycol: modified carbon tube clusters = 1:1, and stirred and mixed. Then, the polyethylene glycol aqueous solution is uniformly infiltrated into the wool ball under -0.50MPa. After the pressure is maintained for 2 hours, the solution is completely infiltrated and slowly heated at 100°C for 5 hours to slowly evaporate the solvent. The polymer is filled in the pores of the modified carbon tube clusters through bonding to obtain a CNT composite carbon material;

[0124] (4) CNT porous carbon: The CNT composite carbon material was placed in a high-temperature furnace, argon gas was introduced at a flow rate of 10 L / min, and the temperature was raised to 800°C at 2°C / min for high-temperature carbonization and pore formation. After carbonization for 10 hours, the furnace was naturally cooled to room temperature while maintaining a protective atmosphere to obtain a sponge-like CNT porous carbon with uniform pore distribution, i.e., a porous elastic composite. The median particle size D of the porous elastic composite is 50 The average pore size is 6.5 μm, the average pore size is 2.62 nm, and the pore volume is 0.98 cm 3 / g, specific surface area is 876.7m 2 / g, pore concentration is 2.5, and tap density is 0.33g / cm 3 , the resistivity is 0.04Ω·cm;

[0125] (5) Preparation of silicon-carbon negative electrode material: The composite material obtained in step (4) is placed in a deposition furnace. After the temperature is raised to 500°C, a mixed gas of silicon source gas and carbon source gas (70% monosilane and 30% acetylene) is introduced into the deposition furnace at a flow rate of 10 L / min. The tail pipe air pressure valve is adjusted and the gas is continuously ventilated for vapor deposition for 5 hours to obtain silicon carbon. The silicon carbon at this time can be directly used as a silicon-carbon composite negative electrode material.

[0126] Preparation process Figure 1 As shown, the SEM images of each stage are shown in Figures 2 to 5 The material performance data of each stage of preparation are shown in Table 1:

[0127] Table 1 Material performance data for each stage

[0128]

[0129] Example 2

[0130] The difference from Example 1 is that: the polymer is phenolic resin;

[0131] (3) Carbon tube composite elastomer: CTAB is added to a phenolic resin-ethanol solution with a solid content of 50%, and then the modified carbon tube clusters are added according to a mass ratio of phenolic resin: modified carbon tube clusters = 1:1, and stirred and mixed. Then, the phenolic resin-ethanol solution is uniformly infiltrated into the wool ball under a state of -0.50MPa. After the pressure is maintained for 2 hours, the solution is completely infiltrated and slowly heated at 120°C for 5 hours to slowly evaporate the solvent. The phenolic resin is filled in the pores of the modified carbon tube clusters through curing and bonding to obtain a carbon tube composite elastomer.

[0132] Example 3

[0133] The difference from Example 1 is that: the polymer is polyimide;

[0134] (3) Carbon tube composite elastomer: CTAB is added to a phenolic resin-NMP solution with a solid content of 50%, and then the modified carbon tube pellets are added according to a mass ratio of polyimide: modified carbon tube pellets = 1:1, stirred and mixed, and then the polyimide-NMP solution is uniformly infiltrated into the wool ball under -0.50MPa. After the pressure is maintained for 2 hours, the solution is completely infiltrated and slowly heated at 120°C for 5 hours to slowly evaporate the solvent. The polyimide is filled in the pores of the modified carbon tube pellets through hydrogen bonding to obtain a CNT composite carbon material.

[0135] Example 4

[0136] The difference from Example 1 is that: the polymer is epoxy resin;

[0137] (3) Carbon tube composite elastomer: CTAB is added to an epoxy resin-toluene solution with a solid content of 50%, and then the carbon tube cluster is added according to the mass ratio of epoxy resin: carbon tube cluster = 1:1, and stirred and mixed. Then, the epoxy resin-toluene solution is uniformly infiltrated into the wool ball at 120°C and -0.50MPa. After maintaining the pressure for 2 hours, the solution is completely infiltrated and slowly cooled to room temperature. The epoxy resin is filled in the pores of the modified carbon tube cluster through curing to obtain a CNT composite carbon material.

[0138] Comparative Example 1

[0139] The difference from Example 1 is that step (3) is not performed and the polymer is not compounded.

[0140] Comparative Example 2

[0141] The difference from Example 1 is that step (4) is not performed and pore making is not performed.

[0142] Comparative Example 3

[0143] The difference from Example 1 is that steps (1) to (3) are not performed, and the carbon source of the porous carbon is replaced by a polymer instead of a carbon tube composite elastomer.

[0144] Batteries were assembled using the negative electrode materials prepared in each embodiment and each comparative example.

[0145] (1) Preparation of positive electrode sheets: The positive electrode active material, lithium nickel cobalt manganese oxide (NCM811), conductive agent Super P, carbon nanotubes, binder polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) were mixed in a mass ratio of 97:1:0.5:1.5 to form a positive electrode slurry (solid content of 70 wt%), which was coated on both sides of the current collector aluminum foil, dried at 100°C, and cold pressed at 4 MPa at room temperature, and then trimmed, cut, and slit, and the tabs were welded to form positive electrode sheets.

[0146] (2) Preparation of negative electrode sheet: Under nitrogen atmosphere, the solvent N-methylpyrrolidone and the binder PVDF were stirred and mixed, and then the conductive agent Super P was added and stirred and mixed, and then the negative electrode active material was added and stirred and mixed thoroughly to prepare a negative electrode slurry (solid content of 50wt%).

[0147] The negative electrode active material is obtained by fully and uniformly mixing the silicon-carbon composite negative electrode materials prepared in the above embodiment and comparative example and graphite so that the gram capacity of the prepared negative electrode material is 450 mAh / g.

[0148] The negative electrode slurry is coated on both sides of the current collector copper foil, dried at 100°C, cold pressed at 4MPa at room temperature, and then trimmed, cut, stripped, and the tabs are welded to make negative electrode sheets.

[0149] (3) Assembly of lithium-ion batteries

[0150] Using PE porous polymer film as a separator, the prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets, and the bare battery cell is wound; the bare battery cell is placed in an aluminum plastic shell package, and dried at 100°C under a relative vacuum pressure of -0.95×105Pa until the moisture content reaches less than 100ppm. The electrolyte is injected into the dried bare battery cell, wherein the electrolyte consists of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) (EC:EMC:DEC volume ratio = 1:1:1) and LiPF6 (1.0M), and the package, static, formation (0.02C constant current charging for 2h, 0.1C constant current charging for 2h), shaping, and capacity testing (capacity separation) are performed to make a soft-pack liquid lithium-ion battery.

[0151] When assembling the battery, five batteries are prepared for each test, and a total of five sets of data are tested. The final performance is the average value of the five sets of data.

[0152] The battery cycle performance is tested on the Xinwei equipment, specifically:

[0153] First coulombic efficiency test: at 25°C, first discharge at 0.1C to 0.005V, then discharge at 0.08C to 0.001V, discharge at 0.05C to 0.001V, discharge at 0.02C to 0.001V, and let stand for 10 minutes; then charge at 0.1C to 1.5V, let stand for 10 minutes, record the charge and discharge capacity after the first cycle, and calculate the first coulombic efficiency;

[0154] Cycle capacity retention rate test: Cycle 500 times in the above manner, record the charge and discharge capacity after 500 cycles, and calculate the capacity retention rate after 500 cycles;

[0155] Rate performance test: Charge at 1C, then discharge at 4C, and test the discharge capacity and capacity retention rate at 1C rate.

[0156] Table 2 Performance of different embodiments and comparative examples

[0157]

[0158] As can be seen from Table 1, in Comparative Example 1, the polymer is not composited, so that the lithium insertion capacity and the capacity retention rate of the silicon-carbon negative electrode material after 500 cycles are not as good as those of Examples 1 to 4. In Comparative Example 2, pores are not formed, so that the lithium insertion capacity, the first coulombic efficiency and the capacity retention rate after 500 cycles are not as good as those of Examples 1 to 4. In Comparative Example 3, steps (1) to (3) are not performed, and the polymer is directly carbonized to prepare porous carbon. Due to the lack of carbon tubes, the conductivity of the negative electrode material deteriorates, thereby significantly reducing the performance.

[0159] In summary, the present application uses wool-like carbon tubes to form macroporous materials to accommodate ordered micro-mesoporous carbon with moderate hardness, and then uses micro-mesoporous materials to accommodate single nano-silicon with excessive hardness. On the one hand, the ordered micro-mesoporous carbon with higher strength belongs to hard carbon, which makes the composite material have higher strength, which can greatly reduce the risk of the negative electrode material being crushed during the rolling process of the pole piece, and improve the safety performance of the pole piece preparation; on the other hand, the flexible carbon tubes make the composite material have certain elasticity and ductility, which can prevent the composite material from falling off from the pole piece due to volume expansion during the charge and discharge process, thereby avoiding the problem of battery cycle diving.

[0160] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present application. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present application. Therefore, all equivalent modifications or changes made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present application.

Claims

1. A porous composite elastomer, which is a porous structure, comprising a flexible body and a rigid body interpenetrating each other, wherein the raw material of the flexible body comprises carbon nanotubes, and the rigid body is hard carbon; the porous composite elastomer contains uniformly distributed micropores and mesopores; the specific surface area of ​​the porous composite elastomer is> 700m 2 / g; the resistivity of the porous composite elastomer is less than 5Ω·cm; the pore size concentration of the porous composite elastomer is less than 7; the total pore volume of the porous composite elastomer is 0.2~1.5cm 3 / g.

2. The porous composite elastomer according to claim 1, characterized in that: The mass ratio of the flexible body to the rigid body is (0.01-2):

1.

3. The porous composite elastomer according to claim 2, characterized in that: Include one or more of the following characteristics: a1) the average pore size of the porous composite elastomer is <15 nm; a2) D of the porous composite elastomer 50 <30 μm; a3) The tap density of the porous composite elastic body is 0.1-1.0 g / cm 3 ; a4) The resistivity of the porous composite elastomer is less than 0.5Ω·cm.

4. The porous composite elastomer according to claim 3, characterized in that: Include one or more of the following characteristics: a1) the average pore size of the porous composite elastomer is 1.8-10 nm; a2) The total pore volume of the porous composite elastomer is 0.4 to 1.1 cm 3 / g; a3) D of the porous composite elastomer 50 <20 μm; a4) The tap density of the porous composite elastomer is 0.2-0.7 g / cm 3 ; a5) the resistivity of the porous composite elastomer is less than 0.05Ω·cm; a6) The pore size concentration of the porous composite elastomer is 0.5~5.

5. A method for preparing a porous composite elastomer according to any one of claims 1 to 4, comprising the following steps: S1: Preparation of carbon tube clusters: shaping carbon nanotubes to form carbon tube clusters; S2: Preparation of carbon tube composite elastomer: adding carbon tube clusters into a solution containing a soft template and a polymer, allowing the solution to penetrate into the carbon tube clusters, and heating and curing to obtain the carbon tube composite elastomer; S3: Preparation of porous composite elastomer: subjecting the carbon tube composite elastomer to high temperature carbonization and activation treatment to obtain a porous composite elastomer.

6. The preparation method according to claim 5, characterized in that: In step S1, the shaping is performed using a shaping machine; And / or, in step S1, the carbon nanotubes have a length of 0.1-50 μm and a tube diameter of 2-20 nm; And / or, in step S1, the carbon tube clusters are spherical or quasi-spherical; And / or, in step S1, the sphericity Sh10% of the carbon tube clusters is ≥ 0.70; And / or, in step S1, the sphericity Sh50% of the carbon tube clusters is ≥ 0.80; And / or, in step S1, the sphericity Sh90% of the carbon tube clusters is ≥ 0.85; And / or, in step S1, the carbon tube cluster D 50 1~100μm; And / or, in step S1, the carbon tube ball is a wool ball-like structure.

7. The preparation method according to claim 6, characterized in that: The main machine frequency of the shaping machine is 5-60 Hz, the auxiliary machine frequency is 20-90 Hz, the fan frequency is 8-30 Hz, and the operation time is 2-100 minutes.

8. The preparation method according to claim 5, characterized in that: An intermediate modification process is also included between step S1 and step S2: adding the carbon tube clusters into an acidic solution and stirring, filtering to obtain a solid, washing to neutrality, and drying to obtain a modified carbon tube cluster.

9. The preparation method according to claim 8, characterized in that: The mass ratio of the carbon tube clusters to the acidic solution is (0.1-100):1; And / or, the acidic solution is selected from one or more of nitric acid, sulfuric acid, and hydrochloric acid; and / or, the stirring reaction temperature is 30-100° C., and the stirring reaction time is 2-12 h; And / or, washing is performed using pure water; drying is performed in a drying oven; And / or, the drying temperature is 60-100° C., and the drying time is 2-48 hours.

10. The preparation method according to claim 5, characterized in that: In step S2, the polymer is selected from one or more of polyethylene glycol, waterborne polyurethane, polyvinyl alcohol, polyvinylidene fluoride, fluorinated copolymer, polyimide, polyacrylic acid, polyacrylate, polymethyl methacrylate, phenolic resin, epoxy resin or ionic resin.

11. The preparation method according to claim 5, characterized in that: In step S2, the soft template is selected from a nonionic surfactant or an ionic surfactant; And / or, in step S2, the mass ratio of the carbon tube clusters to the polymer is (0.1-10):1; And / or, in step S2, the solid content of the polymer in the solution is 20-100%; And / or, in step S2, the solution infiltrates into the carbon tube clusters under negative pressure; And / or, in step S2, the curing temperature is 80-200° C., and the curing time is 0.5-50 h; And / or, in step S2, the solvent needs to be evaporated after solidification to obtain the carbon tube composite carbon material.

12. The preparation method according to claim 11, characterized in that: In step S2, the nonionic surfactant is selected from polyoxyethylene-polyoxypropylene copolymer; and / or, the ionic surfactant is selected from hexadecyltrimethylammonium bromide and / or sodium dodecyl sulfonate; And / or, the negative pressure condition is -0.9~-0.01MPa, and the negative pressure time is 0.5~10h; And / or, negative pressure treatment is followed by positive pressure treatment; the positive pressure condition is 0.15~2MPa, and the pressure holding time is 0.5~48h; And / or, the mass ratio of the carbon tube clusters to the polymer is 1:

3.

13. The preparation method according to claim 5, characterized in that: In step S3, the high temperature carbonization includes subjecting the carbon tube composite carbon material to a high temperature reaction under a protective gas.

14. The preparation method according to claim 13, characterized in that: The protective gas in the high temperature carbonization is selected from one or more of nitrogen, neon, argon, krypton, xenon and radon; And / or, the flow rate of the protective gas is 1-20 L / min; And / or, the temperature of the high temperature reaction is 500-1000°C; And / or, the high temperature reaction time is 1 to 30 hours; And / or, the heating rate of the high temperature reaction is 1-10°C / min; And / or, the high temperature reaction further includes a post-treatment step: cooling to room temperature.

15. A silicon carbon, the raw material of which comprises the porous composite elastomer as claimed in any one of claims 1 to 4, and further comprises nano silicon particles, wherein the nano silicon particles are embedded in the porous composite elastomer.

16. The silicon carbon according to claim 15, characterized in that Include one or more of the following characteristics: b1) The specific surface area of ​​the silicon carbon is less than 20m 2 / g; b2) D of the silicon carbon 50 <20 μm; b3) The tap density of the silicon carbon is 0.5-2 g / cm 3 ; b4) the content of the nano silicon particles is 30-70% of the total mass of silicon carbon; b5) the resistivity of the silicon carbon is less than 20Ω·cm; b6) The specific capacity of the silicon carbon is >1200 mAh / g, the first coulombic efficiency is >89%, the capacity retention rate after 500 cycles is >85%, and the 4C / 1C rate performance is >90%.

17. The method for preparing silicon carbon according to any one of claims 15 to 16, comprising: The porous composite elastomer and silicon-containing source gas are vapor-deposited in a high-temperature environment to obtain silicon carbon.

18. The preparation method according to claim 17, characterized in that: The high temperature environment is a deposition furnace, the high temperature temperature is 300-600°C, and the insulation time is 1-50h; And / or, the silicon source gas is selected from one or more of monosilane, disilane, dichlorosilane, and trichlorosilane; And / or, the silicon-containing source gas further includes a carbon source gas; And / or, the vapor deposition time is 1 to 50 hours.

19. The preparation method according to claim 18, characterized in that: The pressure in the deposition furnace is 5-10 MPa, and the heating rate is 1-5°C / min; And / or, the carbon source gas is selected from alkane gases having a cracking temperature below 600°C; and / or, when the silicon-containing source gas is only silicon source gas, the gas flow rate is 1-20 L / min; And / or, when the silicon-containing source gas includes a silicon source gas and a carbon source gas, based on the total volume of the gas, the volume proportion of the silicon source gas is 70-99%, and the volume proportion of the carbon source gas is 1-30%; and / or, when the silicon-containing source gas includes a silicon source gas and a carbon source gas, the gas flow rate is 5 to 20 L / min; And / or, the vapor deposition time is 10 to 30 hours.

20. A carbon-coated silicon carbon, comprising the silicon carbon according to any one of claims 15 to 16 and a carbon coating layer coated on the surface of the silicon carbon.

21. The carbon-coated silicon carbon according to claim 20, characterized in that The carbon coating amount of the carbon-coated silicon carbon is 0.5-10wt%; And / or, the median particle size D of the carbon-coated silicon carbon 50 <20 μm; And / or, the carbon-coated silicon carbon has a silicon content of 20-80wt%; And / or, the specific surface area of ​​the carbon-coated silicon carbon is 0.5-20.0m 2 / g; And / or, the compacted density of the carbon-coated silicon carbon powder is 0.5-2 g / cm 3 .

22. The method for preparing carbon-coated silicon carbon according to any one of claims 20 to 21, comprising introducing a mixed gas comprising a protective gas and a carbon source gas to coat the silicon carbon to form the carbon-coated silicon carbon.

23. The preparation method according to claim 22, characterized in that: The carbon source gas is selected from alkane gas with a cracking temperature below 600°C; and / or, the protective gas is selected from one or more of nitrogen, neon, argon, krypton, xenon, and radon; and / or, the gas flow rate of the mixed gas is 0.1~50L / min; And / or, based on the total volume of the mixed gas, the volume of the carbon source gas accounts for 60-80%, and the volume of the protective gas accounts for 20-40%.

24. A silicon-carbon composite negative electrode material, wherein the raw material thereof comprises the porous composite elastomer as claimed in any one of claims 1 to 4, the silicon-carbon as claimed in any one of claims 15 to 16, or the carbon-coated silicon-carbon as claimed in any one of claims 20 to 21.

25. Use of the porous composite elastomer according to any one of claims 1 to 4, the silicon-carbon according to any one of claims 15 to 16, the carbon-coated silicon-carbon according to any one of claims 20 to 21, or the silicon-carbon composite negative electrode material according to claim 24 in the preparation of battery products.

26. A lithium-ion battery, wherein the raw materials thereof include the porous composite elastomer according to any one of claims 1 to 4, the silicon-carbon according to any one of claims 15 to 16, the carbon-coated silicon-carbon according to any one of claims 20 to 21, or the silicon-carbon composite negative electrode material according to claim 24.

Citation Information

Patent Citations

  • High-performance silicon-carbon negative electrode material for lithium ion battery, preparation method of silicon-carbon negative electrode material and lithium ion battery

    CN114420928A

  • Carbon nanotube / silicon / carbon composite negative electrode material and preparation method thereof

    CN115663131A